Analisis Tingkat Kebugaran Jasmani Peseta Didik Kelas X SMAN Se Kecamatan Bekasi Utara - Labib Ngizil Khillmiadi; Aridhotul Haqiyah; Dindin Abidin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the physical fitness levels of 10th-grade high school students in the Bekasi Utara Subdistrict using the TKPN (Tes Kebugaran Pelajar Nusantara) instrument. The research employed a quantitative descriptive method with data collection techniques in the form of tests and measurements. The population consisted of 10th-grade students from SMAN 4 Bekasi, SMAN 20 Bekasi, and SMAN 14 Bekasi. The sampling technique used was proportionate stratified random sampling with a total sample of 100 students. The research instrument used was the TKPN (Tes Kebugaran Pelajar Nusantara), which includes Body Mass Index (BMI), V-Sit and Reach, 60-second Sit-Up, 30-second Squat Thrust, and PACER test measurements. Data analysis was conducted using descriptive statistics in the form of percentages. The results showed that most students were in the poor category with 93 students (93%), followed by the fair category with 6 students (6%), and the very poor category with 1 student (1%). No students were classified into the good or excellent categories. The BMI results indicated that the majority of students were in the normal category with 77 students (77%), mildly underweight with 6 students (6%), severely underweight with 3 students (3%), mildly overweight with 5 students (5%), and severely obese with 9 students (9%). Based on the findings, it can be concluded that the physical fitness levels of 10th-grade high school students in the Bekasi Utara Subdistrict are still relatively low, although most students have normal nutritional status. Therefore, increased physical activity and more structured sports programs are needed to improve students' physical fitness levels. Keywords: Physical Activity, Body Mass Index, Physical Fitness, High School Students, TKPN